DO CORPORATE GOVERNANCE AND MACROECONOMIC FACTORS INFLUENCE THE LEVERAGE OF BRAZILIAN COMPANIES LISTED ON B3? - Flávia Barbosa de Brito Araújo; Eunice Henriques Pereira Vilela; Duterval Jesuka; Antônio Sergio Torres Penedo (Revista Gestão em Análise, 2022)
This study aims to analyze the influence of Corporate Governance mechanisms and macroeconomic factors concerning the leverage of Brazilian companies listed on B3. The model proposes the use of Artificial Neural Networks in conjunction with multiple linear regression with panel data. The period of analysis covers the years from 2010 to 2018, and the sample is composed of 619 companies, totaling 5571 observations. Data was collected from Reference Forms (FR), Economática, and annual reports. As a result, the ANN model presented satisfactory predictive performance, and through this, no influence of Governance and Macroeconomic Factors variables on the companies' leverage was observed, contrary to the existing literature. On the other hand, the regression model partly confirms with the literature, mainly for variables related to board composition and annual growth at the country level.